A participatory needs assessment to map the system dynamics of overweight related behaviours of 10-14-year-old adolescents living in an underserved neighbourhood in Amsterdam, the Netherlands - Helga Emke; Rabab Chrifou; Coosje Dijkstra; Wilma Waterlander; Karien Stronks; Stef Kremers; Mai Chinapaw; Teatske Altenburg (BMC Public Health)
Abstract Background Developing interventions along with the population of interest using systems thinking is a promising method to address the underlying system dynamics of overweight. The purpose of this study is twofold: to gain insight into the perspectives of adolescents regarding: (1) the system dynamics of energy balance-related behaviours (EBRBs) (physical activity, screen use, sleep behaviour and dietary behaviour); and (2) underlying mechanisms and overarching drivers of unhealthy EBRBs. Methods We conducted Participatory Action Research (PAR) to map the system dynamics of EBRBs together with adolescents aged 10–14 years old living in a lower socioeconomic, ethnically diverse neighbourhood in Amsterdam East, the Netherlands. For just over two years, we conducted weekly PAR sessions (45–120 min) with four dynamic groups - two in primary schools and two in secondary schools - each school year (n = 4–8 adolescents in each group (0-100% girls); n = 40–54 sessions in total per group). These adolescents acted as co-researchers and created Causal Loop Diagrams (CLDs) for each EBRB and explored important underlying mechanisms for unhealthy EBRBs. Based on the underlying mechanisms, three overarching drivers for unhealthy EBRBs were distinguished. Results The three overarching drivers for unhealthy EBRBs are: (1) the physical environment, (2) social norms, and (3) unhealthy behaviours reinforcing each other. The adolescents explained that their physical environment fosters unhealthy behaviour by providing easy access to unhealthy food products while restricting physical activity. They explained the importance of social norms around EBRBs that are formed by their peers, friends, and family. The influence of their peers often led to unhealthier EBRBs, especially after the transition to secondary school. The adolescents explained that unhealthy behaviours reinforced each other, while healthy behaviour led to more healthy behaviour. Conclusions Our novel approach combining PAR with systems thinking gained valuable insights into the system dynamics of EBRBs from the adolescent perspective. These insights can inform future interventions targeting systems change regarding EBRBs.